Interfacial Engineering and Photon Downshifting of CsPbBr3 Nanocrystals for Efficient, Stable, and Colorful Vapor Phase Perovskite Solar Cells. Issue 11 (20th April 2019) - Chen, Cong; Wu, Yanjie; Liu, Le; Gao, Yanbo; Chen, Xinfu; Bi, Wenbo; Chen, Xu; Liu, Dali; Dai, Qilin; Song, Hongwei
Abstract: Photovoltaic devices employing lead halide perovskites as the photoactive layer have attracted enormous attention due to their commercialization potential. Yet, there exists challenges on the way to the practical use of perovskite solar cells (PSCs), such as light stability and current–voltage ( J – V ) hysteresis. Inorganic perovskite nanocrystals (IPNCs) are promising candidates for high‐performance photovoltaic devices due to their simple synthesis methods, tunable bandgap, and efficient photon downshifting effect for ultraviolet (UV) light blocking and conversion. In this work, CsPbBr3 IPNCs modification could give rise to the vapor phase and solution‐processed PSCs with a power conversion efficiency (PCE) of 16.4% and 20.8%, respectively, increased by 11.6% and 5.6% compared to the control devices for more efficient UV utilization and carrier recombination suppression. As far as is known, 11.6% is the most effective enhanced factor for PSCs based on photon downshifting effect inside of devices. The CsPbBr3 layer could also significantly retard light‐induced degradation, leading to the lifetime over 100 h under UV illumination for PSCs. Additionally, the modified PSCs exhibit weak hysteresis and multiple colors of fluorescence. These results shed light on the future design of combining a photon downshifting layer and carrier interfacial modification layer in the applications of perovskite optoelectronic devices. Abstract : Inorganic perovskite quantum dots can be used as efficient luminescent down converting layers for ultraviolet blocking and conversion in traditional perovskite solar cells. In this work, a new cell configuration by integrating CsPbBr3 inside of device structure is demonstrated. The modified devices could exhibit weak hysteresis, improved photoelectric performance, and multiple colors of fluorescence.